Programa de habilidades sociais assertivas com idosos: avaliação sob delineamento placebo - Braz, Ana Carolina (Universidade Federal de São Carlos, 2010)
Given current social concerns with respect to senior´s rights, this study describes and evaluates a Social-Skills Assertiveness Training-Program (ASSTP) for elderly people. The sample (two men and 13 women) participated in one of two intervention groups: Experimental (EG, which received the ASSTP) or Placebo (PG, which received educational interactive presentations), based on a placebo design. For pre, post-test and follow-up measures, participants were evaluated using the IHSI-Del-Prette (a Social Skills inventory for the elderly) and the IREI (a questionnaire for the evaluation of the extent to which elderly people understand and exercise their rights). Also, during the post-test, participants completed a program evaluation questionnaire User´s Satisfaction with the Training Program . Results indicated acquisition and maintenance of the assertiveness social-skills repertoire in the EG, but not in the PG. Assessments carried out in the pre, post and followup using the IREI multiple choice items indicated no differences between these results in either EG or the PG. For the requiring written responses, however qualitative questions of IREI statiscally significant differences were found for Spontaneous reports of senior rights (for the EG, but not the for PG) and for Discrimination of situations when elderly had their rights disrespected by others , between the posttest and follow-up results for both the EG and the PG. With respect to their satisfaction, both groups presented high means for: (1) satisfaction with the program received, (2) importance of the program´s procedures, (3) readiness to perform assertive social skills, and (4) self evaluation of their performance in the program, but the PG indicated higher levels of satisfaction than the EG. We discuss the impact and effectiveness of the ASST Program, the viability and the importance of using placebo designs in order to assess internal validity of social-skills assertiveness training-programs and its critical features, as well as the relevance of this kind of intervention for the elderly, at this time.
Social-skills assertiveness training-program: evaluation below a placebo study design
Keywords: Idosos - psicologia; Habilidades sociais - avaliação e intervenção; Envelhecimento - aspectos psicológicos; Delineamento placebo; Assertive social skills; Elderly; Placebo design; CIENCIAS HUMANAS::PSICOLOGIA